2016
DOI: 10.1111/pai.12552
|View full text |Cite
|
Sign up to set email alerts
|

Cesarean section delivery and development of food allergy and atopic dermatitis in early childhood

Abstract: Delivery by CS predisposes to the development of food allergy but not atopic dermatitis in early childhood. Cesarean section delivery seems to upregulate the immune response to food allergens, especially in children with allergic predisposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
63
0
13

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 34 publications
11
63
0
13
Order By: Relevance
“…Greek birth cohort study showed that children born by CS had a threefold higher probability of FA in the first 3 years of life, especially those with allergic predisposition. 24 No effect was shown on the risk of AD, in agreement with previous findings. 18 Along this line, as antibiotics are frequently prescribed during the neonatal period among preterm infants, an antibiotic-induced delay in intestinal bacterial colonization may increase the risk for developing allergic disorders.…”
Section: Perinatal Influencessupporting
confidence: 91%
See 1 more Smart Citation
“…Greek birth cohort study showed that children born by CS had a threefold higher probability of FA in the first 3 years of life, especially those with allergic predisposition. 24 No effect was shown on the risk of AD, in agreement with previous findings. 18 Along this line, as antibiotics are frequently prescribed during the neonatal period among preterm infants, an antibiotic-induced delay in intestinal bacterial colonization may increase the risk for developing allergic disorders.…”
Section: Perinatal Influencessupporting
confidence: 91%
“…Delivery by cesarean section (CS) may predispose the development of FA in early childhood presumably due to the lack of exposure to vaginal and perianal bacteria. A prospective Greek birth cohort study showed that children born by CS had a threefold higher probability of FA in the first 3 years of life, especially those with allergic predisposition . No effect was shown on the risk of AD, in agreement with previous findings .…”
Section: Perinatal Influencessupporting
confidence: 86%
“…Often, skin manifestations like atopic dermatitis (AD; or eczema) appear in infancy and can persist into adulthood. It is estimated that AD affects up to 20% of the population, especially in developed countries (15), and predisposes children to the development of food allergies in early childhood and to asthma by school age (16)(17)(18)(19)(20). This disease progression is often called the atopic or allergic march.…”
mentioning
confidence: 99%
“…Delivery by cesarean section may predispose the newborn baby to FA, presumably due to modifications in the establishment of gut microbiota caused by a different initial exposure to microbes (59, 60). Continuous intake of antibiotics has a profound influence on the bacterial composition that colonize the intestinal track, which may affect the allergic response to food and which seems to be essential for the maintenance of homeostasis (61, 62).…”
Section: Genetic and Environmental Factors Involved In Famentioning
confidence: 99%